Response of Sediment Microbial Communities to the Rural Wastewater in the Pond-Ditch Circulation System - Yu, Mengfei; Pan, Yongtai; Yang, Lingli; Liu, Wei; He, Feng; Ma, Lin (Frontiers in Environmental Science, 2021)
Microorganisms played important roles in nutrient removal in Pond-ditch circulation system (PDCS). However, dynamics of microbial community in the PDCS, and responses of rhizosphere and non-rhizosphere microbial community to rural wastewater remains unclear. In this paper, average operational taxonomic units numbers of sediment microbial varied from 10254 to 17112, and values in rhizosphere were higher than those of the non-rhizosphere (P<0.05). Bacillus, Clostridium sensu stricto 1, and Geobacter were the predominant genera in PDCS sediment with relative abundances of 0.52%-17.61%, 0.26%-8.08%, and 0.20%-4.58%, respectively. However, Bacillus, Clostridium sensu stricto 1, and Geobacter genera in rhizosphere were more abundant than those in non-rhizosphere at day 30. Chao 1 index ranged from 10225 to 17033 and showed significant positive correlations with all sediment properties (P<0.05). Chao 1 and Shannon indices in rhizosphere were significant positively related to tartaric acid and total organic carbon, respectively; while significant correlation between Shannon and Simpson indices in non-rhizosphere and oxidation-reduction potential were detected (P<0.05). Redundancy analysis suggested that lactic acids, proteins, and amino acids had strong positive effects on Geobacter and Clostridiu sensu stricto 12 in the rhizosphere; while Bacillus and Clostridium in non-rhizosphere were significantly affected by sediment ammonia nitrogen and nitrate nitrogen. Environmental variables accounted for 66.9% and 60.3% of the total variation for the microbial community of non-rhizosphere and rhizosphere sediments, respectively. Our results highlight that root exudates and sediment available N alter predominant genera in the rhizosphere and non-rhizosphere, respectively, which is benefit for optimizing removal efficiency of PDCSs in large-scale applications.